2022
DOI: 10.1093/lambio/ovac056
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the growth-inhibitory activity of postbiotics of Lactobacillus spp. against Staphylococcus aureus under in vitro circumstances and food model

Abstract: Postbiotics are soluble metabolites that are liberated from the structure of lysing bacteria or are produced by live bacteria; these byproducts give the host increased biological activity and certain physiological effects. In the current study, the anti-Staphylococcus properties of postbiotics isolated from Lactobacillus acidophilus,L.paracasei,and L.plantarum were investigated in vitro, and pasteurized milk. Potential activity of postbiotics was performed via agar-disk diffusion method. Besides, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These compounds offer a promising approach to combating food-borne pathogens, reducing oxidative stress and inflammatory response, strengthening the gut barrier, and/or regulating the host immune system (Aggarwal et al, 2022 ). Lactiplantibacillus spp.-derived postbiotics (cell-free supernatants) showed strong antioxidant activity and anti- Staphylococcus properties, which were mainly associated with lactic acid and other antibacterial components (Khani et al, 2023 ). Lactic acid bacteria (LAB) postbiotics also exhibited high antioxidant capacity and total phenolic content; combinations with natural preservatives such as EDTA could reduce food-borne pathogens (Incili et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds offer a promising approach to combating food-borne pathogens, reducing oxidative stress and inflammatory response, strengthening the gut barrier, and/or regulating the host immune system (Aggarwal et al, 2022 ). Lactiplantibacillus spp.-derived postbiotics (cell-free supernatants) showed strong antioxidant activity and anti- Staphylococcus properties, which were mainly associated with lactic acid and other antibacterial components (Khani et al, 2023 ). Lactic acid bacteria (LAB) postbiotics also exhibited high antioxidant capacity and total phenolic content; combinations with natural preservatives such as EDTA could reduce food-borne pathogens (Incili et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postbiotics are commonly prepared by culturing the LAB in culture media [mainly de Man, Rogosa, and Sharpe (MRS) broth], followed by an extraction step (centrifugation or dialysis and filtration) (Gomez-Sala et al, 2016 ; Dunand et al, 2019 ; Barros et al, 2020 ; Moradi et al, 2021 ), and other fermentation alternatives such as milk and milk-related media also successfully produced remarkable antifungal activity (Gamier et al, 2019 ). Most studies revealed the antibacterial or antioxidant functions of postbiotics from submerged fermentation (Rossoni et al, 2020 ; Kienesberger et al, 2022 ; Banakar et al, 2023 ; Khani et al, 2023 ); however, they barely illustrated the SSF or developed multifunctional postbiotics. Moreover, studies on the preparation of functional postbiotics by solid-state fermentation with LAB and Bacillus strains or their combination for the production of potential antibacterial, antioxidant, and anti-inflammatory postbiotics are lacking.…”
Section: Introductionmentioning
confidence: 99%